EBOOK PEDOMAN PERSIAPAN PERNIKAHAN - Jannah, Miftahul; Azizah, Siti Nur; Wahdah, Issania; Puadah, Popi (Journal Education and Government Wiyata, 2024)
Marriage is part of half a religion and is also the longest worship in human life that everyone looks forward to. Therefore, every prospective bride and groom hopes that their wedding can be prepared according to their wishes and expectations. Wedding preparations involve many aspects and most young couples may still not understand the proper steps to prepare for their wedding. The aim of this research is to analyze the factors of readiness for marriage in young couples and examine their impact on the age of marriage, as well as assessing readiness for marriage. So, with the e-book, marriage preparation guidelines, we can provide guidance and information that is easy to understand for young couples who are getting married in preparing for marriage in order to form a sakinah, mawaddah, warahmah family.